The Ability of Current Operating Income to Predict Future Operating Cash Flows over the Time - Hamid Khaleghi Moghaddam; Elham Hamidi (مطالعات تجربی حسابداری مالی, 2007)
In this research, we examine the value relevance of accounting information over the time in order to use it in valuation models. For this reason, the ability of current operating Income to predict oneyear-ahead operating cash flows has been examined by means of annual cross-sectional regression approach from 1378 to 1385. Then the degree of relationship between operating Income and operating cash flows is investigated.  The results show that both operating Income and operating cash flows have the ability to predict one-year ahead operating cash flows. But the incremental explanatory power of operating Income over operating cash flows is significant. Then in order to test the value relevance of accounting information over the time, we investigate the relationship between R2ₑ , R2 inc-e, R2 ocf, R2 inc-ocf, and lime by means  of nonparametric statistics. The results do not show any significant relationship between  R2ₑ , R2 inc-e, R2 ocf, R2 inc-ocf and time ROI t  - ROI t-1.